Display system and display body
Patent Information
- Application Number
- CN202580015484.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-19
- Filing Date
- 2025-01-29
- Publication Date
- 2026-10-02
Smart Images

Figure CN122872864A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a display system and a display body. Background Technology
[0002] Image display devices, represented by liquid crystal displays and electroluminescent (EL) displays (e.g., organic EL displays), are rapidly gaining popularity. In image display devices, optical components such as polarizing components and phase difference components are generally used to achieve image display and improve image display performance (e.g., see Patent Document 1).
[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays for Virtual Reality (VR) (VR goggles) have begun to be commercialized. As the use of VR goggles in various scenarios is being researched, there is a desire for them to be lighter and more precise. Lighter weight can be achieved, for example, by making the lenses used in VR goggles thinner. On the other hand, there is also a desire to develop optical components suitable for display systems that use thin lenses.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-103286 Summary of the Invention
[0007] The problem the invention aims to solve
[0008] In view of the above, the main objective of the present invention is to provide a display system that enables the realization of lightweight and high-precision VR goggles.
[0009] Problem Solving Methods
[0010] 1. The display system according to an embodiment of the present invention is a display system for displaying images to a user, the display system comprising: a display element having a display surface from which light for displaying an image is emitted forward via a polarizing member; a reflective portion disposed in front of the display element, including a reflective polarizing member, and reflecting light emitted from the display element; a first lens portion disposed in the optical path between the display element and the reflective portion; a semi-reflective mirror disposed between the display element and the first lens portion, allowing light emitted from the display element to pass through and reflecting light after reflection by the reflective portion toward the reflective portion; a first phase difference member disposed in the optical path between the display element and the semi-reflective mirror; a first member disposed in the optical path between the display element and the semi-reflective mirror; a second phase difference member disposed in the optical path between the semi-reflective mirror and the reflective portion; and a second member disposed in the optical path between the semi-reflective mirror and the reflective portion. The first phase difference component and the second phase difference component are respectively phase difference components capable of converting linearly polarized light into circularly polarized light or converting circularly polarized light into linearly polarized light. The first component and the second component are respectively components that impart a phase difference in the thickness direction. Between the display element and the semi-reflective mirror and between the semi-reflective mirror and the reflective part, the following conditions are met: the component that imparts a phase difference in the thickness direction is located in front of or behind the phase difference component, and the phase difference in the thickness direction of the first component is different from the phase difference in the thickness direction of the second component.
[0011] 2. In the display system described in 1 above, the absolute value of the difference between the phase difference Rth(590) in the thickness direction of the first component and the phase difference Rth(590) in the thickness direction of the second component can be 10 nm or more.
[0012] 3. In the display system described in 1 or 2 above, the component that imparts a phase difference in the thickness direction can be a positive C-plate.
[0013] 4. In the display system described in any one of 1 to 3 above, the surface smoothness of each of the first phase difference member, the second phase difference member, the first member, and the second member is 1.0 arcmin or less.
[0014] 5. In the display system described in any one of 1 to 4 above, the ellipticity of the transmitted light with a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° can be 0.77 or higher for the first optical stack and the second optical stack, respectively. The first optical stack includes the polarizing member, the first phase difference member, and the first member, and the second optical stack includes the reflecting part, the second phase difference member, and the second member.
[0015] 6. In the display system described in any one of 1 to 5 above, the ellipticity of the transmitted light at a wavelength of 550 nm measured at a polar angle of 0° for the first optical stack and the second optical stack can be 0.94 or higher, the first optical stack includes the polarizing member, the first phase difference member and the first member, and the second optical stack includes the reflective part, the second phase difference member and the second member.
[0016] 7. In the display system described in any one of 1 to 6 above, the value (1-DI) obtained by subtracting the depolarization index (DI) of the transmitted light with a wavelength of 550 nm measured at a polar angle of 0° from 1 for the first optical laminate and the second optical laminate can be 95.5% or more, wherein the first optical laminate includes the polarization member, the first phase difference member and the first member, and the second optical laminate includes the reflective portion, the second phase difference member and the second member.
[0017] 8. The display system described in any one of 1 to 7 above may include a second lens portion disposed in front of the reflective portion.
[0018] 9. The display body of the embodiment of the present invention includes the display system described in any one of 1 to 8 above.
[0019] The effects of the invention
[0020] The display system according to an embodiment of the present invention enables the VR goggles to be lightweight and highly precise. Attached Figure Description
[0021] Figure 1 This is a schematic diagram illustrating a simplified configuration of a display system according to one embodiment of the present invention.
[0022] Figure 2 It is a schematic illustration of the configuration in Figure 1 A diagram illustrating an example of the positional relationship between the display element and the reflective part of the display system.
[0023] Figure 3 It is a schematic illustration of the configuration in Figure 1 A diagram showing another example of the positional relationship between the display element and the reflective part of the display system.
[0024] Figure 4 This is a diagram showing the brightness in the configuration of the laminates of the embodiments and comparative examples.
[0025] Symbol Explanation
[0026] 2 Display System
[0027] 12 display elements
[0028] 14. Reflector
[0029] 16 First Lens Section
[0030] 18 Semi-reflective mirrors
[0031] 20 First phase difference component
[0032] 22 Second phase difference component
[0033] 24 Second Lens Section
[0034] 30 Component 1
[0035] 32 Component 2
[0036] 100 First optical laminate
[0037] 200 Second optical laminate Detailed Implementation
[0038] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. For clarity, the drawings sometimes schematically show the width, thickness, shape, etc., of various parts compared to the embodiments, but these are merely examples and do not limit the interpretation of the present invention. Furthermore, regarding the drawings, sometimes the same or equivalent elements are labeled with the same symbols, and repeated descriptions are omitted.
[0039] (Definitions of terms and symbols)
[0040] The terms and symbols used in this manual are defined as follows.
[0041] (1) Refractive index (nx, ny, nz)
[0042] “nx” is the refractive index in the direction where the refractive index reaches its maximum in the plane (i.e., the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0043] (2) In-plane phase difference (Re)
[0044] “Re(λ)” is the in-plane phase difference measured at 23°C with light of wavelength λnm. For example, “Re(550)” is the in-plane phase difference measured at 23°C with light of wavelength 550nm. When the thickness of the layer (film) is set as d (nm), Re(λ) can be obtained by the formula: Re(λ)=(nx-ny)×d.
[0045] (3) Phase difference (Rth) in the thickness direction
[0046] “Rth(λ)” is the phase difference in the thickness direction measured at 23°C using light with a wavelength of λnm. For example, “Rth(550)” is the phase difference in the thickness direction measured at 23°C using light with a wavelength of 550nm. When the thickness of the layer (film) is set as d (nm), Rth(λ) can be obtained using the formula: Rth(λ)=(nx-nz)×d.
[0047] (4) Nz coefficient
[0048] The coefficient of Nz can be obtained by Nz = Rth / Re.
[0049] (5) Angle
[0050] In this specification, when referring to angles, unless otherwise specified, the angle includes both clockwise and counterclockwise directions relative to a reference direction. Therefore, for example, "45°" means ±45°. Furthermore, in this specification, "generally parallel" includes a range of 0°±10°, preferably 0°±5°, more preferably 0°±3°, and even more preferably 0°±1°. "Generally orthogonal" includes a range of 90°±10°, preferably 90°±5°, more preferably 90°±3°, and even more preferably 90°±1°.
[0051] Figure 1 This is a schematic diagram illustrating a simplified configuration of a display system according to one embodiment of the present invention. Figure 1 The diagram schematically illustrates the configuration and shape of the various components of the display system 2. The display system 2 includes a display element 12, a reflective portion 14 including a reflective polarizing member, a first lens portion 16, a semi-reflective mirror 18, a first phase difference member 20, a second phase difference member 22, and a second lens portion 24. The reflective portion 14 is disposed on the display surface 12a side, i.e., in front of the display element 12, and is capable of reflecting light emitted from the display element 12. The first lens portion 16 is disposed in the optical path between the display element 12 and the reflective portion 14, and the semi-reflective mirror 18 is disposed between the display element 12 and the first lens portion 16. The first phase difference member 20 is disposed in the optical path between the display element 12 and the semi-reflective mirror 18, and the second phase difference member 22 is disposed in the optical path between the semi-reflective mirror 18 and the reflective portion 14.
[0052] The display element 12 is, for example, a liquid crystal display or an organic EL display, having a display surface 12a for displaying images. Light emitted from the display surface 12a passes through a polarizing member (typically a polarizing film) that may be included in the display element 12 and is then emitted as first linearly polarized light.
[0053] The first phase difference member 20 can convert the first linearly polarized light incident on the first phase difference member 20 into the first circularly polarized light. The first phase difference member 20 can be integrally disposed on the display element 12.
[0054] The semi-reflective mirror 18 allows light emitted from the display element 12 to pass through, and reflects the light that has been reflected by the reflective portion 14 towards the reflective portion 14. Figure 1 In the example shown, the semi-reflective mirror 18 is integrally disposed on the first lens section 16.
[0055] The second phase difference member 22 allows light that has been reflected by the reflector 14 and the half-reflector 18 to pass through the reflector 14, which includes a reflective polarizing member. The second phase difference member 22 can be integrally disposed on the first lens portion 16 or integrally disposed on the second lens portion 24. In the latter case, the second phase difference member 22 can be integrally disposed on the second lens portion 24 together with the reflector 14.
[0056] The first circularly polarized light emitted from the first phase difference member 20 passes through the half-reflector 18 and the first lens section 16, and is converted into second linearly polarized light by the second phase difference member 22. The second linearly polarized light emitted from the second phase difference member 22 is reflected back to the half-reflector 18 without passing through the reflective polarizing member included in the reflecting section 14. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarizing member included in the reflecting section 14 is the same as the reflection axis of the reflective polarizing member. Therefore, the second linearly polarized light incident on the reflecting section 14 is reflected by the reflective polarizing member.
[0057] The second linearly polarized light, after being reflected by the reflecting section 14, is converted into second circularly polarized light by the second phase difference member 22. The second circularly polarized light emitted from the second phase difference member 22 passes through the first lens section 16 and is reflected by the half-reflecting mirror 18. The circularly polarized light, after being reflected by the half-reflecting mirror 18, passes through the first lens section 16 and is converted into third linearly polarized light by the second phase difference member 22. The third linearly polarized light passes through the reflective polarizing member included in the reflecting section 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member included in the reflecting section 14 is the same as the transmission axis of the reflective polarizing member. Therefore, the third linearly polarized light incident on the reflecting section 14 will pass through the reflective polarizing member.
[0058] Light that has passed through the reflector 14 passes through the second lens 24 and enters the user's eye 26.
[0059] For example, the absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member included in the reflective portion 14 can be arranged in a manner that is approximately parallel to each other, or they can be arranged in a manner that is approximately orthogonal to each other.
[0060] Although not in Figure 1 As shown, the display system 2 may include a first member disposed in the optical path between the display element 12 and the semi-reflective mirror 18, imparting a phase difference in the thickness direction. Additionally, the display system 2 may include a second member disposed in the optical path between the semi-reflective mirror 18 and the reflective portion 14, imparting a phase difference in the thickness direction. By providing such a member, light leakage (e.g., oblique light leakage) can be prevented. Furthermore, the so-called ghosting phenomenon, which is visually perceived as image overlap, can be reduced.
[0061] Figure 2 It is a schematic illustration of the configuration in Figure 1 The diagram shows an example of the positional relationship between the display element and the reflective part of the display system. Figure 3 It is a schematic illustration of the configuration in Figure 1 A diagram showing another example of the positional relationship between the display element and the reflective part of the display system.
[0062] exist Figure 2 In the example shown, in front of the polarizing member 10 included in the display element 12 ( Figure 2 On the right side), a first phase difference member 20 and a first member 30 that imparts a phase difference in the thickness direction are arranged sequentially. Furthermore, behind the reflective portion 14 ( Figure 2 On the left side, a second member 32 and a second phase difference member 22, which impart a phase difference in the thickness direction, are sequentially arranged. The members 30 and 32, which impart a phase difference in the thickness direction, are respectively positioned further forward than the phase difference members 20 and 22. The polarizing member 10, the first phase difference member 20, and the first member 30 can be stacked to form a first optical laminate 100. Furthermore, the reflecting portion 14, the second member 32, and the second phase difference member 22 can be stacked to form a second optical laminate 200. It should be noted that in... Figure 2 The first lens portion 16 and the semi-reflective mirror 18 are not shown in the figure. They may be disposed, for example, between the first member 30 and the second phase difference member 22.
[0063] exist Figure 3 In the example shown, in front of the polarizing member 10 included in the display element 12 ( Figure 2 On the right side), a first member 30 and a first phase difference member 20, which impart a phase difference in the thickness direction, are arranged sequentially. Furthermore, behind the reflective portion 14 ( Figure 2On the left side, a second phase difference member 22 and a second member 32 imparting a phase difference in the thickness direction are sequentially arranged. The members 30 and 32 imparting a phase difference in the thickness direction are respectively positioned further rearward than the phase difference members 20 and 22. The polarizing member 10, the first member 30, and the first phase difference member 20 can be stacked to form a first optical laminate 100. Furthermore, the reflecting portion 14, the second phase difference member 22, and the second member 32 can be stacked to form a second optical laminate 200. It should be noted that in... Figure 3 The first lens portion 16 and the half-reflector 18 are not shown in the figure. They may be disposed, for example, between the first phase difference member 20 and the second member 32.
[0064] exist Figure 2 and Figure 3 In any example, when the first phase difference member 20 and the second phase difference member 22 are considered as the same member, and the first member 30 and the second member 32 are considered as the same member, they can be considered to be in a non-symmetrical configuration with respect to the surface M indicated by the dashed line (an asymmetrical configuration). By adopting such a configuration, light leakage (e.g., oblique light leakage) can be prevented more effectively, and ghosting can be reduced more effectively.
[0065] In one embodiment, an optical component assembly having a first optical stack 100 and a second optical stack 200 may be provided.
[0066] In both the first optical laminate 100 and the second optical laminate 200 (hereinafter, sometimes simply referred to as optical laminates), the components constituting the optical laminate can be laminated via any suitable adhesive layer. By laminating the components via adhesive layers, an optical laminate with excellent smoothness can be obtained. In the above-described display system, the image is magnified at the lens section (e.g., via a convex lens), and the smoothness of the optical laminate can significantly affect visual recognition. Based on the optical laminate with excellent smoothness, significantly superior visual recognition can be achieved in the above-described display system.
[0067] The adhesive layer described above can be formed by an adhesive or a binder. Specifically, the adhesive layer can be an adhesive layer or a binder layer. The thickness of the adhesive layer is, for example, 0.05 μm to 30 μm.
[0068] The first phase difference component 20 and the second phase difference component 22 (hereinafter, sometimes simply referred to as phase difference components) can each be a phase difference component capable of converting linearly polarized light into circularly polarized light, or vice versa. The phase difference components can be composed of a single layer or have a stacked structure.
[0069] When the phase difference component is composed of a single layer, it can be a λ / 4 component in a typical case. The in-plane phase difference Re(550) of the λ / 4 component can be, for example, 100nm~190nm, 110nm~180nm, 130nm~160nm, or 135nm~155nm.
[0070] The λ / 4 element preferably exhibits an inverse dispersion wavelength characteristic, where the phase difference increases with the wavelength of the measurement light. The Re(450) / Re(550) of the λ / 4 element is, for example, less than 1, and can be 0.95 or less, further less than 0.90, and further less than 0.85. The Re(450) / Re(550) of the λ / 4 element is, for example, 0.75 or more.
[0071] In one embodiment, the λ / 4 member satisfies all the conditions Re(400) / Re(550) < 0.85, Re(650) / Re(550) > 1.03, and Re(750) / Re(550) > 1.05. The λ / 4 member preferably satisfies at least one of the following conditions, more preferably at least two, and even more preferably all of the following conditions: 0.65 < Re(400) / Re(550) < 0.80 (preferably 0.7 < Re(400) / Re(550) < 0.75), 1.0 < Re(650) / Re(550) < 1.25 (preferably 1.05 < Re(650) / Re(550) < 1.20), and 1.05 < Re(750) / Re(550) < 1.40 (preferably 1.08 < Re(750) / Re(550) < 1.36).
[0072] The refractive index characteristics of the preferred λ / 4 component exhibit a relationship of nx > ny ≥ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Therefore, ny < nz is sometimes permissible without impairing the effects of the present invention. The Nz coefficient (Rth(590) / Re(590)) of the λ / 4 component is preferably 0.4 to 3, more preferably 0.4 to 2.5, further preferably 0.4 to 1.5, and particularly preferably 0.4 to 1.3.
[0073] The λ / 4 component is formed from any suitable material capable of satisfying the above characteristics. For example, the λ / 4 component can be a stretched film of a resin film or an alignment fixing layer of a liquid crystal compound. It should be noted that the stretched film of the resin film is sometimes referred to as a retardation film.
[0074] Examples of resins included in the aforementioned resin films include: polycarbonate resins, polyester carbonate resins, polyester resins, polyvinyl acetal resins, polyarylate resins, cyclic olefin resins, cellulose resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, and acrylic resins. These resins can be used alone or in combination (e.g., blending, copolymerization). When the λ / 4 component exhibits inverse dispersive wavelength characteristics, resin films containing polycarbonate resins or polyester carbonate resins (hereinafter, sometimes simply referred to as polycarbonate resins) can be suitably used.
[0075] As the aforementioned polycarbonate resin, any suitable polycarbonate resin can be used as long as the effects of the present invention are achieved. For example, the polycarbonate resin comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from at least one dihydroxy compound selected from alicyclic diols, alicyclic diethanols, di-, tri-, or polyethylene glycols, and alkylene diols or spirodiols. Preferably, the polycarbonate resin comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from alicyclic diethanols and / or structural units derived from di-, tri-, or polyethylene glycols; more preferably, it comprises structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from di-, tri-, or polyethylene glycols. The polycarbonate resin may also, as needed, comprise structural units derived from other dihydroxy compounds. It should be noted that details of the polycarbonate resins suitable for use in λ / 4 components and the methods for forming λ / 4 components are described, for example, in Japanese Patent Application Publication Nos. 2014-10291, 2014-26266, 2015-212816, 2015-212817, and 2015-212818, and these publications are incorporated herein by reference.
[0076] The aforementioned alignment-fixing layer of the liquid crystal compound is a layer in which the liquid crystal compound is aligned in a given direction within the layer, and its alignment state is fixed. It should be noted that "alignment-fixing layer" includes the concept of an alignment-cured layer obtained by curing liquid crystal monomers as described later. For the λ / 4 component, typically, rod-shaped liquid crystal compounds are aligned (homogeneous alignment) in a state aligned along the slow axis direction of the λ / 4 component. Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably capable of polymerization. If the liquid crystal compound is capable of polymerization, then by polymerization after aligning the liquid crystal compound, the alignment state of the liquid crystal compound can be fixed.
[0077] The alignment layer (liquid crystal alignment layer) of the aforementioned liquid crystal compound can be formed by the following method: an alignment treatment is performed on the surface of a given substrate; a coating liquid containing the liquid crystal compound is applied to the surface; the liquid crystal compound is aligned along a direction corresponding to the alignment treatment; and the alignment state is fixed. Any suitable alignment treatment can be used. Examples include mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment. Specific examples of mechanical alignment treatment include friction treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include tilting vapor deposition and photo-alignment treatment. The processing conditions for each alignment treatment can be any suitable condition depending on the purpose.
[0078] The orientation of a liquid crystal compound can be achieved by processing it at a temperature that displays a liquid crystal phase, depending on the type of liquid crystal compound. Through such temperature processing, the liquid crystal compound is in a liquid crystal state and is oriented in accordance with the orientation processing direction of the substrate surface.
[0079] In one embodiment, the orientation state is fixed by cooling the oriented liquid crystal compound as described above. If the liquid crystal compound is polymerizable or crosslinkable, the orientation state can be fixed by performing a polymerization or crosslinking treatment on the oriented liquid crystal compound as described above.
[0080] As the aforementioned liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer can be used. The liquid crystal polymer and liquid crystal monomer can be used alone or in combination. Specific examples of liquid crystal compounds and methods for fabricating liquid crystal alignment fixing layers are described, for example, in Japanese Patent Application Publication No. 2006-163343, Japanese Patent Application Publication No. 2006-178389, and International Publication No. 2018 / 123551. The contents of these publications are incorporated herein by reference.
[0081] The thickness of the λ / 4 component, which is formed by stretching a resin film, is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and even more preferably 20 μm to 50 μm. Furthermore, the thickness of the λ / 4 component, which is formed by a liquid crystal alignment fixing layer, is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and even more preferably 1 μm to 4 μm.
[0082] The angle between the absorption axis of the polarization member 10 and the slow axis of the first phase difference member 20, which is a λ / 4 member, is, for example, 40°~50°, 42°~48°, or approximately 45°. The angle between the absorption axis of the polarization member 10 and the slow axis of the second phase difference member 22, which is a λ / 4 member, is, for example, 40°~50°, 42°~48°, or approximately 45°.
[0083] In the case where the phase difference component has a stacked structure, the phase difference component typically has a stacked structure comprising λ / 2 layers and λ / 4 layers.
[0084] The in-plane phase difference Re(550) of the λ / 2 layer can be, for example, 200nm~330nm, 230nm~330nm, 230nm~290nm, or 250nm~280nm.
[0085] The in-plane phase difference Re(550) of the λ / 4 layer can be, for example, 100nm~200nm, 110nm~180nm, 130nm~160nm, or 135nm~155nm.
[0086] Each of the λ / 2 and λ / 4 layers (hereinafter, sometimes simply referred to as layers included in the stacked structure) preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference increases with the wavelength of the measurement light. The Re(450) / Re(550) of the layers included in the stacked structure is, for example, 0.75 or more and less than 1, and can be 0.8 or more and less than 0.95.
[0087] The layers contained in the stacked structure can also exhibit flat wavelength dispersion characteristics, where the phase difference value is substantially independent of the wavelength of the measured light. In this case, the Re(450) / Re(550) of the layers contained in the stacked structure can be, for example, 0.99 to 1.03, and the Re(650) / Re(550) can be, for example, 0.98 to 1.02.
[0088] The refractive index characteristics of the layers included in the laminated structure preferably exhibit a relationship of nx > ny ≥ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Therefore, it is permissible to have ny < nz without impairing the effects of the present invention. The Nz coefficient (Rth(550) / Re(550)) of the layers included in the laminated structure is preferably 0.4 to 3, more preferably 0.4 to 2.5, even more preferably 0.4 to 1.5, and particularly preferably 0.4 to 1.3.
[0089] The layers in the laminated structure are formed from any suitable material capable of satisfying the above-mentioned characteristics. For example, the layers in the laminated structure can be a stretched film of a resin film or an alignment fixing layer of a liquid crystal compound. Details of the stretched film of the resin film and the alignment fixing layer of the liquid crystal compound are described above. When the layers in the laminated structure have flat wavelength dispersion characteristics, cycloolefin resins are preferably preferred as forming materials, with norbornene resins being particularly preferred.
[0090] Norbornene resins are resins polymerized from norbornene monomers. Examples of norbornene monomers include: norbornene and its alkyl and / or alkylene substituents, such as 5-methyl-2-norbornene, 5-dimethyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 5-ethylidene-2-norbornene, and their halogenated or other polar substituents; dicyclopentadiene, 2,3-dihydrodicyclopentadiene, etc.; dimethylbridged octahydronaphthalene, etc. Its alkyl and / or alkylene substituents, as well as polar group substituents such as halogens, for example, 6-methyl-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethyl-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethylene-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a- Octahydronaphthalene, 6-chloro-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-cyano-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-pyridyl-1,4:5,8-dimethylbridged-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-methoxycarbonyl-1,4:5,8-dimethylbridged-1 4,4a,5,6,7,8,8a-octahydronaphthalene, etc.; 3- to 4-quadrimers of cyclopentadiene, such as 4,9:5,8-dimethylbridged-3a,4,4a,5,8,8a,9,9a-octahydro-1H-benzo[a]indene, 4,11:5,10:6,9-trimethylbridged-3a,4,4a,5,5a,6,9,9a,10,10a,11,11a-dodecylhydro-1H-cyclopentanthene, etc. The above norbornene resins can also be copolymers of norbornene monomers with other monomers.
[0091] Regarding the thickness of the λ / 4 layer, the description of the λ / 4 component described above can be applied. The thickness of the λ / 2 layer, which is formed by stretching a resin film, is, for example, 20 μm to 200 μm, preferably 20 μm to 140 μm, more preferably 20 μm to 120 μm, and even more preferably 40 μm to 100 μm. Furthermore, the thickness of the λ / 2 layer, which is formed by a liquid crystal alignment fixing layer, is, for example, 2 μm to 20 μm, preferably 2 μm to 16 μm, more preferably 2 μm to 12 μm, and even more preferably 2 μm to 8 μm.
[0092] In the phase difference component, the angle between the slow axis of the λ / 2 layer and the slow axis of the λ / 4 layer is preferably 50° to 70°, more preferably 55° to 65°, further preferably 57° to 63°, and particularly preferably about 60°. In one embodiment, the angle between the absorption axis of the polarizing component 10 and the slow axis of the λ / 2 layer is preferably 5° to 35°, more preferably 10° to 20°, further preferably 12° to 18°, and particularly preferably about 15°. The angle between the absorption axis of the polarizing component 10 and the slow axis of the λ / 4 layer is preferably 55° to 85°, more preferably 70° to 80°, further preferably 72° to 78°, and particularly preferably about 75°. In another embodiment, the angle between the absorption axis of the polarizing component 10 and the slow axis of the λ / 4 layer is preferably 5° to 35°, more preferably 10° to 20°, further preferably 12° to 18°, and particularly preferably about 15°. The angle between the absorption axis of the polarizing member 10 and the slow axis of the λ / 2 layer is preferably 55° to 85°, more preferably 70° to 80°, even more preferably 72° to 78°, and particularly preferably about 75°.
[0093] The first phase difference member 20 and the second phase difference member 22 can be members with the same structure (forming material, thickness, optical properties, etc.) or members with different structures. For example, from the point of view of manufacturing efficiency, the first phase difference member 20 and the second phase difference member 22 can adopt the same structure.
[0094] In display system 2, for example, from the viewpoint of improving visual recognizability, it is required to highly adjust the phase difference value of the first phase difference member 20 and the phase difference value of the second phase difference member 22. For example, the absolute value of the difference between the in-plane phase difference (a) of the first phase difference member 20 and the in-plane phase difference (b) of the second phase difference member 22 is, for example, 3.5 nm or less, preferably 3.0 nm or less, more preferably 2.5 nm or less, further preferably 2.0 nm or less, particularly preferably 1.5 nm or less, and most preferably 1.0 nm or less. (a) and (b) are, for example, values of Re(590).
[0095] Additionally, for example, the in-plane phase difference (a) of the first phase difference member 20 and the in-plane phase difference (b) of the second phase difference member 22 preferably satisfy the following formula (I).
[0096] ((a)-(b)) / ((a)+(b) / 2)≤0.02···(I)
[0097] More preferably, ((a)-(b)) / ((a)+(b) / 2)≤0.015, and even more preferably, ((a)-(b)) / ((a)+(b) / 2)≤0.01.
[0098] Typically, the first member 30 and the second member 32 that impart a phase difference in the thickness direction (hereinafter, sometimes simply referred to as members imparting a phase difference in the thickness direction) can each be a member whose refractive index characteristics can show the relationship nz > nx = ny (so-called positive C plate).
[0099] The phase difference Rth(590) in the thickness direction of the positive C-plate is, for example, less than -10 nm, preferably -20 nm to -200 nm, more preferably -30 nm to -180 nm, even more preferably -40 nm to -160 nm, and particularly preferably -50 nm to -140 nm. Here, "nx = ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane phase difference Re(550) of the positive C-plate is, for example, less than 10 nm.
[0100] The positive C-plate is formed from any suitable material that can satisfy the above characteristics. For example, the positive C-plate can be an alignment fixing layer of a resin film or a liquid crystal compound.
[0101] Representative examples of resin films constituting the positive C-plate include resin materials with negative birefringence. Resins with negative birefringence exhibit the property that their refractive index is highest in the direction perpendicular to the stretching direction when subjected to uniaxial stretching. Examples of resins with negative birefringence include those with highly polarized anisotropic chemical bonds and functional groups such as aromatic rings and carbonyl groups introduced into their side chains. Specific examples of resins with negative birefringence include acrylic resins, styrene resins, maleimide resins, modified polyolefin resins, and fumarate resins. Specific examples can be found in Japanese Patent Application Publication Nos. 2021-076759, 2008-544304, and 2008-544317. These resin materials can be used alone or in combination of two or more.
[0102] The resin film constituting the positive C-plate may further contain any suitable additives as needed. Specific examples of additives include: plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, UV absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, thickeners, etc. The type and content of additives can be appropriately set according to the purpose. The content of additives in the resin film is, for example, approximately 3% to 10% by weight.
[0103] In one embodiment, the resin material can be directly used as a positive C-plate after being formed into a film. Specifically, the film can be used directly as a positive C-plate without stretching it. For example, when a resin solution containing the resin material is coated onto a support (using a solution film-forming method), stress is generated due to the volume shrinkage of the resin solution during drying on the support, resulting in a tendency for the polymer molecular chains to orient in the in-plane direction. When using a resin material with high birefringence and negative intrinsic birefringence, a coating with large thickness-direction birefringence can be formed on the support through the shrinkage during drying. Moreover, the formed coating can be used directly as a positive C-plate.
[0104] The thickness of the positive C-plate made of resin film is, for example, 1 μm to 40 μm, preferably 3 μm to 35 μm, and more preferably 5 μm to 30 μm.
[0105] As the alignment fixing layer of the liquid crystal compound constituting the positive C-plate, an alignment fixing layer of liquid crystal material fixed in a vertical orientation is preferably exemplified. The liquid crystal material (liquid crystal compound) capable of vertical orientation can be a liquid crystal monomer or a liquid crystal polymer. As a specific example of such a liquid crystal compound and a method for forming the positive C-plate, the liquid crystal compound and the method for forming the phase retardation layer described in paragraphs 0020 to 0028 of Japanese Patent Application Publication No. 2002-333642 can be cited.
[0106] The thickness of the positive C-plate, which is composed of an alignment fixing layer of liquid crystal compound, is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0107] The first component 30 and the second component 32 can each adopt any suitable configuration. Preferably, the phase difference in the thickness direction of the first component 30 is different from the phase difference in the thickness direction of the second component 32. By adopting such a configuration, light leakage (e.g., oblique light leakage) can be prevented more effectively, and ghosting can be reduced more effectively. The absolute value of the difference between the phase difference Rth(590) in the thickness direction of the first component 30 and the phase difference Rth(590) in the thickness direction of the second component 32 is, for example, 5 nm or more, preferably 10 nm or more, more preferably 25 nm or more, and even more preferably 40 nm or more. The absolute value of the difference between the phase difference Rth(590) in the thickness direction of the first component 30 and the phase difference Rth(590) in the thickness direction of the second component 32 is, for example, 120 nm or less, preferably 110 nm or less, more preferably 100 nm or less, and even more preferably 90 nm or less.
[0108] like Figure 2 As shown, when the components 30 and 32 that impart a phase difference in the thickness direction are positioned further forward than the phase difference components 20 and 22, the phase difference in the thickness direction of the second component 32 is preferably greater than the phase difference in the thickness direction of the first component 30. Figure 3 As shown, when the components 30 and 32 that impart a phase difference in the thickness direction are respectively positioned further back than the phase difference components 20 and 22, the phase difference in the thickness direction of the first component 30 is preferably greater than the phase difference in the thickness direction of the second component 32.
[0109] The surface smoothness of the phase difference member and the member imparting the phase difference in the thickness direction is, for example, 1.0 arcmin or less, preferably 0.50 arcmin or less, more preferably 0.40 arcmin or less, even more preferably 0.30 arcmin or less, and particularly preferably 0.20 arcmin or less. Within such a range, a display system with excellent visual recognizability can be achieved. For example, by satisfying such surface smoothness, the uniformity of the phase difference value can be improved, resulting in a display system with excellent display characteristics.
[0110] The thickness deviation of the phase difference member and the member imparting the phase difference in the thickness direction is preferably 1 μm or less, more preferably 0.8 μm or less, even more preferably 0.6 μm or less, and even more preferably 0.4 μm or less. With such a thickness deviation, for example, the aforementioned surface smoothness can be well achieved. Here, the thickness deviation can be determined by measuring the thickness of a first portion located within the surface of the object being measured, and the thickness at a position separated from the first portion by a given interval (e.g., 5 mm to 15 mm) in any direction (e.g., above, below, left, and right).
[0111] The polarizing element 10 can typically be an absorptive polarizing element containing a resin film (sometimes called an absorptive polarizing film) containing a dichroic substance. The absorptive polarizing element typically has a laminated structure of an absorptive polarizing film and a protective layer.
[0112] The thickness of the absorption polarizing film can be, for example, 1 μm or more and 20 μm or less, 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.
[0113] The aforementioned absorptive polarizing film can be made from a single layer of resin film or from a laminate of two or more layers.
[0114] In the case of a single-layer resin film, for example, an absorbing polarizing film can be obtained by subjecting hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films to dyeing treatments using dichroic substances such as iodine and dichroic dyes, and stretching treatments. Among these, an absorbing polarizing film obtained by dyeing a PVA film with iodine and then uniaxially stretching it is preferred.
[0115] The above-mentioned dyeing using iodine can be carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after dyeing or during dyeing. Alternatively, dyeing can be performed after stretching. Swelling treatment, crosslinking treatment, cleaning treatment, drying treatment, etc., can be applied to the PVA film as needed.
[0116] Examples of laminates made using two or more layers include a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a resin substrate and a PVA-based resin layer coated on the resin substrate. An absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be manufactured by: for example, coating a PVA-based resin solution onto a resin substrate, drying it to form a PVA-based resin layer on the resin substrate, obtaining a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to form an absorptive polarizing film from the PVA-based resin layer. In this embodiment, it is preferable to form a polyvinyl alcohol resin layer comprising a halide and a polyvinyl alcohol resin on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, stretching may, as needed, further include stretching the laminate in a gas atmosphere at a high temperature (e.g., 95°C or higher) before stretching in the aqueous boric acid solution. Furthermore, in this embodiment, it is preferable to subject the laminate to a drying shrinkage treatment, which involves heating it while transporting it along its length to shrink it by 2% or more in its width direction. Typically, the manufacturing method of this embodiment includes sequentially subjecting the laminate to assisted stretching in a gas atmosphere, dyeing, stretching in an aqueous solution, and drying shrinkage treatment. By introducing assisted stretching, even when PVA is coated on a thermoplastic resin substrate, the crystallinity of PVA can be improved, resulting in high optical properties. Additionally, by simultaneously improving the orientation of PVA beforehand, problems such as decreased orientation and dissolution of PVA during subsequent dyeing and stretching processes when immersed in water can be prevented, further achieving high optical properties. Moreover, when the PVA-type resin layer is immersed in a liquid, compared to cases where the PVA-type resin layer does not contain halides, the orientation disorder of polyvinyl alcohol molecules and the reduction of orientation can be suppressed. Therefore, the optical properties of the absorption polarizing film obtained by immersing the laminate in a liquid through dyeing and stretching processes in an aqueous solution can be improved. Furthermore, by drying and shrinking the laminate in the width direction, optical properties can be improved. The resulting resin substrate / absorbent polarizing film laminate can be used directly (i.e., the resin substrate can be used as a protective layer for the absorbent polarizing film), or the resin substrate can be peeled off from the resin substrate / absorbent polarizing film laminate, and any suitable protective layer corresponding to the purpose can be laminated on the peeled surface or on the side opposite to the peeled surface. Detailed descriptions of such a method for manufacturing an absorbent polarizing film are described, for example, in Japanese Patent Application Publication No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.
[0117] The orthogonal transmittance (Tc) of the absorptive polarizing film (absorbent polarizing member) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The monomer transmittance (Ts) of the absorptive polarizing film (absorbent polarizing member) is, for example, 41.0% to 45.0%, preferably 42.0% or more. The degree of polarization (P) of the absorptive polarizing film (absorbent polarizing member) is, for example, 99.0% to 99.997%, preferably 99.9% or more.
[0118] The reflective polarizing member included in the reflective section 14 allows polarized light parallel to its transmission axis (typically linearly polarized light) to pass through while maintaining its polarization state, and reflects light with other polarization states (typically light orthogonal to its transmission axis). The reflective polarizing member is typically composed of a film with a multilayer structure (sometimes called a reflective polarizing film). The thickness of the reflective polarizing film is, for example, 10 μm to 150 μm, preferably 20 μm to 100 μm, and more preferably 30 μm to 60 μm.
[0119] Commercially available reflective polarizing films include, for example, those manufactured by 3M under the brand names "DBEF" and "APF", and those manufactured by Nitto Denko Corporation under the brand name "APCF".
[0120] The orthogonal transmittance (Tc) of the reflective polarizing element (reflective polarizing film) can be, for example, 0.01% to 3%. The single-unit transmittance (Ts) of the reflective polarizing element (reflective polarizing film) can be, for example, 43% to 49%, preferably 45% to 47%. The degree of polarization (P) of the reflective polarizing element (reflective polarizing film) can be, for example, 92% to 99.99%.
[0121] In addition to a reflective polarizing member, the reflective portion 14 may also include an absorptive polarizing member. The absorptive polarizing member may be positioned in front of the reflective polarizing member. The reflection axis of the reflective polarizing member and the absorption axis of the absorptive polarizing member may be arranged approximately parallel to each other, and the transmission axis of the reflective polarizing member and the transmission axis of the absorptive polarizing member may also be arranged approximately parallel to each other. When the reflective portion 14 includes an absorptive polarizing member, it may also include a laminate containing both a reflective polarizing member and an absorptive polarizing member.
[0122] The ellipticity of the transmitted light at a wavelength of 550 nm, measured at a polar angle of 30° and an azimuth angle of 0° to 360°, is preferably 0.77 or higher, more preferably 0.78 or higher, even more preferably 0.80 or higher, particularly preferably 0.82 or higher, and most preferably 0.84 or higher. Using an optical stack exhibiting such an ellipticity, a display system with excellent display characteristics can be obtained. According to such an optical stack, ghosting can be reduced in the aforementioned display system. Furthermore, light leakage can be suppressed, contributing to high resolution. A higher ellipticity of the transmitted light at a wavelength of 550 nm, measured at a polar angle of 30° and an azimuth angle of 0° to 360°, is preferred, with an upper limit of, for example, 0.90 (preferably 0.93, more preferably 0.95, and even more preferably 0.99). Here, "ellipticity" is the ratio of the minor axis to the major axis of circularly polarized light, and is an absolute value. For example, the ellipticity is 1 when the light is completely circularly polarized; and 0 when the light is completely linearly polarized.
[0123] In one embodiment, the ellipticity of transmitted light of a given wavelength, measured at a polar angle of 30° and an azimuth angle of 0° to 360°, is the ellipticity measured every 11.25° azimuth angle within the range of 0° to 360°, with light of the given wavelength incident from the polarizing member side at a polar angle of 30° and for the outgoing light at a polar angle of 30°. Therefore, "ellipticity of X or higher" measured at an azimuth angle of 0° to 360° means that the minimum of the 32 measured values is X.
[0124] The ellipticity of the transmitted light at a wavelength of 550 nm, measured at a polar angle of 0° (front view), is preferably 0.94 or higher, more preferably 0.95 or higher, and even more preferably 0.96 or higher. Within this range, an optical laminate with significant effects of reducing ghosting, suppressing light leakage, and achieving high precision can be obtained. A higher ellipticity of the transmitted light at a wavelength of 550 nm, measured at a polar angle of 0° (front view), is preferred, with an upper limit of, for example, 0.99 (preferably 1).
[0125] The aforementioned ellipticity can be measured, for example, using a Mueller matrix polarization measuring instrument (manufactured by Axometrics, product name "Axoscan"), at 23°C, by incident light of a given wavelength (e.g., 550 nm) from the polarization member side of the optical laminate.
[0126] The value (1-DI) obtained by subtracting the depolarization index (DI) of the aforementioned optical laminate from 1 is preferably 60% or more. For the depolarization index (DI), the Mueller matrix representing the polarization effect (hereinafter (1)) can be measured and obtained according to the following formula (2). The Mueller matrix representing the polarization effect can be measured, for example, using a Mueller matrix polarization measuring instrument (manufactured by Axometrics, product name "Axoscan"), at 23°C, by incident light of a given wavelength (e.g., 550 nm) from the polarization member side of the optical laminate.
[0127] [Mathematical Expression 1]
[0128]
[0129] The value (1-DI) obtained by subtracting the depolarization index (DI) of transmitted light with a wavelength of 550 nm measured at a polar angle of 30° and an azimuth angle of 0° to 360° from 1 for the aforementioned optical laminate is preferably 99.68% or higher. Here, the depolarization index (DI) of a given wavelength measured at a polar angle of 30° and an azimuth angle of 0° to 360° is the average value of the depolarization index measured at 11.25° intervals within the azimuth angle range of 0° to 360°, for light of a given wavelength incident from the polarizing member side of the optical laminate at a polar angle of 30° and for the outgoing light at a polar angle of 30°. The value (1-DI) obtained by subtracting the depolarization index (DI) of transmitted light with a wavelength of 550 nm measured at a polar angle of 0° (front direction) for the aforementioned optical laminate is preferably 99.5% or higher, and more preferably 99.75% or higher.
[0130] Example
[0131] The present invention will now be described in detail with reference to specific embodiments, but the present invention is not limited to these embodiments in any way. It should be noted that the testing and evaluation methods in the embodiments, etc., are described below.
[0132] (1) Thickness
[0133] Thicknesses below 10 μm were measured using a scanning electron microscope (manufactured by Nippon Electron Ltd., product name "JSM-7100F"). Thicknesses exceeding 10 μm were measured using a digital micrometer (manufactured by Anritsu Ltd., product name "KC-351C").
[0134] (2) Phase difference
[0135] The phase difference at a given wavelength was measured using a phase difference / elliptic polarization measurement device (manufactured by Oji Measurement Equipment Co., Ltd., product name "KOBRA-HBR", "KOBRA-HBPR") at 23°C.
[0136] (3) Monomeric transmittance and polarization degree of polarizing film
[0137] The monomer transmittance (Ts), parallel transmittance (Tp), and orthogonal transmittance (Tc) of the polarizing film were measured using a spectrophotometer (Otsuka Electronics Co., Ltd., "LPF-200"). These Ts, Tp, and Tc values were measured using a 2-degree field of view (C-light source) according to JIS Z8701 and were Y values corrected for visibility. Based on the obtained Tp and Tc, the degree of polarization of the polarizing film was calculated using the following formula.
[0138] Degree of polarization (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0139] (4) Surface smoothness
[0140] Smoothness was measured using a phase-shifted laser interferometer (Zygo Corporation, product name "DynaFiz"). Specifically, the test object was laminated onto a microscope slide (Matsunami Glass Industry Co., Ltd., product name "S200200") to prevent the introduction of foreign matter, air bubbles, or deformed streaks. Next, to remove the influence of tiny air bubbles, degassing was performed using a pressure degassing device (autoclave). The degassing conditions were set at 50°C, 0.5 MPa, and 30 minutes. After degassing, the sample was allowed to cool naturally at room temperature for at least 30 minutes to obtain the test sample.
[0141] The test sample was placed on a measuring platform equipped with a vibration damping stage. A single-wavelength laser (633 nm) was used to interfere with a reference device whose flatness was ensured, and the relative displacement within a given area (a circle with a diameter of 30 mm) was measured. For the analysis, the surface smoothness (unit: arcmin) was defined as the surface smoothness obtained by multiplying the angle index "Slope magnitude RMS" (derived from the extraction of values at frequencies from 0.1 / mm to 1 / mm) by 2.
[0142] [Manufacturing Example 1: Fabrication of a Phase Retardation Film]
[0143] A batch polymerization unit consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled at 100°C was fed with 29.60 parts by weight (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluorene-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spirodiol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC), and 1.19 × 10⁻⁶ mol of calcium acetate monohydrate as a catalyst. -2 Parts by weight (6.78 × 10) -5(mol). After purging the reactor with nitrogen under reduced pressure, heating was performed using a heat transfer medium. Stirring was initiated when the internal temperature reached 100°C. The internal temperature was raised to 220°C 40 minutes after the start of heating. While maintaining this temperature, the pressure was reduced, reaching 13.3 kPa after 90 minutes. Phenolic vapors produced as a byproduct of the polymerization reaction were introduced into a 100°C reflux condenser, allowing a certain amount of monomer components contained in the phenol vapors to return to the reactor, while the uncondensed phenol vapors were recovered in a 45°C condenser. Nitrogen was introduced into the first reactor to temporarily restore atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Then, heating and depressurization were initiated in the second reactor, reaching an internal temperature of 240°C and a pressure of 0.2 kPa after 50 minutes. Polymerization was then allowed to proceed until the given stirring power was reached. At the moment when the given power is reached, nitrogen is introduced into the reactor to restore the pressure, the generated polyester carbonate resin is extruded into the water, and the wire is cut to obtain granules.
[0144] The obtained polyester carbonate resin (granules) was vacuum dried at 80°C for 5 hours, and then a strip resin film with a thickness of 130 μm was produced using a film-forming apparatus equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder set temperature: 250°C), a T-die (width 200 mm, set temperature: 250°C), a chilled roll (set temperature: 120~130°C), and a winding machine. The obtained strip resin film was stretched along its width at a stretching temperature of 140°C and a stretch ratio of 2.7.
[0145] Thus, a phase retardation film with a thickness of 47 μm, a Re(590) of 143 nm, and an Nz coefficient (Rth(590) / Re(590)) of 1.2 was obtained. The Re(450) / Re(550) of the obtained phase retardation film is 0.859. In addition, the surface smoothness of the phase retardation film is 0.25 arcmin.
[0146] [Manufacturing Example 2: Formation of the Positive C-Panel]
[0147] A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (1) (where the numbers 65 and 35 represent the molar percentage of monomer units, and for convenience, it is represented in the form of a block polymer with a weight-average molecular weight of 5000), 80 parts by weight of a polymerizable liquid crystal (manufactured by BASF: trade name Paliocolor LC242) displaying a nematic liquid crystal phase, and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone.
[0148] [Chemical Formula 1]
[0149]
[0150] The prepared coating solution was applied to a substrate film (norbornene resin film, manufactured by Zeon Corporation, Japan, trade name "ZEONEX") using a bar coater, and then heated and dried at 80°C for 4 minutes to align the liquid crystal. The liquid crystal layer was then cured by irradiating it with ultraviolet light, thus forming a positive C-plate (thickness: 0.5μm~8μm, surface smoothness: 0.13arcmin~0.23arcmin) with a refractive index characteristic of nz>nx=ny and an Rth(590) in the range of -10nm~-160nm on the substrate film. Details of the obtained positive C-plate are shown in Table 1. It should be noted that the Rth(450) / Rth(550) of the obtained positive C-plate is 1.072, exhibiting positive dispersion wavelength characteristics.
[0151]
[0152] [Manufacturing Example 3: Fabrication of Polarizing Film]
[0153] As a thermoplastic resin substrate, a strip-shaped amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) with a Tg of about 75 °C was used to apply corona treatment to one side of the resin substrate.
[0154] A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, trade name "GOHSENX Z410") in a 9:1 ratio, and dissolving the resulting mixture in water.
[0155] The above-mentioned PVA aqueous solution was coated on the corona-treated surface of the resin substrate and dried at 60°C, thereby forming a PVA resin layer with a thickness of 13 μm and producing a laminate.
[0156] The resulting laminate was stretched unidirectionally along the longitudinal direction (length direction) to 2.4 times in an oven at 130°C (assisted stretching treatment in a gas atmosphere).
[0157] Next, the laminate is immersed in an insoluble bath (an aqueous solution of boric acid prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (insoluble treatment).
[0158] Next, for the laminate, in order to achieve the desired monomer transmittance (Ts) of the final absorptive polarizing film, the concentration was adjusted while immersing it in a staining bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds (staining treatment).
[0159] Next, the laminate was immersed in a crosslinking bath (an aqueous solution of boric acid prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (crosslinking treatment).
[0160] Then, while immersing the laminate in a boric acid aqueous solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is unidirectionally stretched (stretching treatment in aqueous solution) between rollers with different circumferential speeds along the longitudinal direction (length direction) to achieve a total stretch ratio of 5.5.
[0161] Then, the laminate was immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution of 100 parts by weight of water and 4 parts by weight of potassium iodide) (cleaning treatment).
[0162] Then, while drying in an oven maintained at approximately 90°C, the laminate is subjected to drying on SUS heated rollers that maintain the contact surface temperature at approximately 75°C (drying shrinkage treatment). The width-direction shrinkage rate of the laminate based on the drying shrinkage treatment is 5.2%.
[0163] Thus, an absorptive polarizing film with a thickness of approximately 5 μm was formed on the resin substrate.
[0164] A cyclic olefin resin film (thickness: 25 μm) as a protective layer was bonded to the surface of the obtained absorptive polarizing film (the side opposite to the resin substrate) using a UV-curable adhesive. Specifically, the adhesive was applied to achieve a total thickness of approximately 1 μm and then bonded using a roller press. UV light was then irradiated from the cyclic olefin resin film side to cure the adhesive. The resin substrate was then peeled off.
[0165] Thus, a polarizing film composed of a cyclic olefin resin film / absorption polarizing film was obtained. The monomer transmittance (Ts) of the polarizing film is 43.4%, and the degree of polarization is 99.993%.
[0166] [Manufacturing Example 4: Fabrication of Optical Laminate A]
[0167] After the positive C-plate is bonded to the phase retardation film via an adhesive layer with a thickness of 1 μm, the substrate film is removed from the positive C-plate to obtain the laminate.
[0168] On the retardation film side of the obtained laminate, the polarizing film is bonded via an adhesive layer with a thickness of 5 μm to obtain optical laminate A. At this time, the polarizing film is bonded such that the absorption axis of the polarizing film is at a 45° angle to the slow axis of the retardation film. Furthermore, the absorptive polarizing film of the polarizing film is bonded such that its absorption type is located on the retardation film side.
[0169] [Manufacturing Example 5: Fabrication of Optical Laminate B]
[0170] After the positive C-plate is bonded to the phase retardation film via an adhesive layer with a thickness of 1 μm, the substrate film is removed from the positive C-plate to obtain the laminate.
[0171] On the positive C-plate side of the obtained laminate, the aforementioned polarizing film is bonded via an adhesive layer with a thickness of 5 μm to obtain optical laminate B. At this time, the bonding is performed such that the absorption axis of the polarizing film is at a 45° angle to the slow axis of the retardation film. Furthermore, the absorption-type polarizing film of the polarizing film is bonded such that its absorption type is located on the positive C-plate side.
[0172] <Evaluation>
[0173] As shown in Table 2, the two laminates obtained in the above manufacturing example are arranged vertically with their polarizing films positioned on the outer edges. Using the absorption axis of the polarizing film of the upper laminate as a reference (0°), the laminates are arranged such that, relative to this reference, the slow axis of the retardation film of the upper laminate is at an angle of 45°, the absorption axis of the polarizing film of the lower laminate is at an angle of 90°, and the slow axis of the retardation film of the lower laminate is at an angle of 135°.
[0174] It should be noted that, since both absorptive and reflective polarizing components can allow linearly polarized light to pass through while preventing linearly polarized light orthogonal to it from passing through, for convenience, an absorptive polarizing component was also used in the polarizing components included in the upper laminate for evaluation purposes.
[0175]
[0176] The backlight was turned on from the bottom side of the lower stack, and the brightness of the light emitted from the upper stack was measured using a conograph (manufactured by AUTRONIC MELCHRS).
[0177] As the backlight, a UV-LED irradiator with dimming via a UV constant current control power supply (LPDC series manufactured by AITEC SYSTEM, adjustment parameters: COARSE2 / FINE8) was used.
[0178] With the incident and exit angles set to a polar angle of 30°, the luminance (cd / m²) was measured every 5° azimuth angle within the range of 0° to 355°. 2 ), calculate the average of the obtained values.
[0179] For each configuration shown in Table 2, the Rth(590) of the positive C-plate was changed and measurements were taken. The results (average brightness, unit: cd / m²) were recorded. 2 The results are summarized in Tables 3 and 4.
[0180] In Table 3, the Rth(590) of the positive C-plates contained in each stacked structure configured vertically is set to be substantially the same (Rth(590): -10nm~-160nm). It should be noted that the results are the same in configuration 1 and configuration 2.
[0181] Table 4 shows the measurement results for configurations 1 and 2 shown in Table 2, where the Rth(590) of the positive C-plate located above configuration 1 and below configuration 2 varies in the range of -10 nm to -160 nm, and the difference between 0 nm and 90 nm is greater than that of the Rth(590) of the other positive C-plate. It should be noted that the results are the same in configurations 1 and 2.
[0182]
[0183] In configurations 1 and 2 shown in Table 2, when the Rth(590) of the positive C-plate is -110nm, the luminance is 52.0 cd / m². 2 In contrast, in the configuration of Comparative Example 1, when the Rth(590) of the positive C-plate is -80 nm, the luminance is 60.2 cd / m². 2 In configurations 1 and 2 shown in Table 2, lower brightness can be achieved by adjusting the phase difference in the thickness direction of the positive C-plate.
[0184]
[0185] exist Figure 4 The measurement results are shown in Table 4.
[0186] This invention is not limited to the embodiments described above, and various modifications are possible. For example, it can be replaced with a configuration that is substantially the same as the configuration shown in the above embodiments, a configuration that performs the same function, or a configuration that achieves the same purpose.
[0187] Industrial applicability
[0188] The display system of the present invention can be used, for example, in display devices such as VR goggles.
Claims
1. A display system for displaying images to a user, The display system includes: A display element having a display surface from which light for displaying an image is emitted forward via a polarizing member; A reflective element, disposed in front of the display element, includes a reflective polarizing member and reflects light emitted from the display element; A first lens portion is disposed in the optical path between the display element and the reflective portion; A semi-reflective mirror is disposed between the display element and the first lens portion, allowing light emitted from the display element to pass through and causing light that has been reflected by the reflective portion to be reflected toward the reflective portion; A first phase difference component is disposed in the optical path between the display element and the semi-reflective mirror; The first component is disposed in the optical path between the display element and the semi-reflective mirror; A second phase difference component is disposed in the optical path between the semi-reflective mirror and the reflective part; as well as The second component is positioned in the optical path between the semi-reflective mirror and the reflective part. The first phase difference component and the second phase difference component are respectively phase difference components capable of converting linearly polarized light into circularly polarized light, or circularly polarized light into linearly polarized light. The first component and the second component are respectively components that impart a phase difference in the thickness direction. Both between the display element and the semi-reflective mirror, and between the semi-reflective mirror and the reflective portion, satisfy the following condition: the component imparting a phase difference in the thickness direction is located in front of or behind the phase difference component. The phase difference in the thickness direction of the first component is different from the phase difference in the thickness direction of the second component.
2. The display system according to claim 1, wherein, The absolute value of the difference between the phase difference Rth(590) in the thickness direction of the first component and the phase difference Rth(590) in the thickness direction of the second component is greater than 10 nm.
3. The display system according to claim 1, wherein, The component that imparts a phase difference in the thickness direction is a positive C-plate.
4. The display system according to claim 1, wherein, The surface smoothness of the first phase difference component, the second phase difference component, the first component, and the second component is below 1.0 arcmin.
5. The display system according to claim 1, wherein, The ellipticity of transmitted light at a wavelength of 550 nm, measured at a polar angle of 30° and an azimuth angle of 0°~360°, is greater than 0.77 for both the first and second optical stacks. The first optical laminate includes the polarization member, the first phase difference member, and the first member. The second optical laminate includes the reflective portion, the second phase difference member, and the second member.
6. The display system according to claim 1, wherein, The ellipticity of transmitted light at a wavelength of 550 nm, measured at a polar angle of 0°, is greater than 0.94 for both the first and second optical stacks. The first optical laminate includes the polarization member, the first phase difference member, and the first member. The second optical laminate includes the reflective portion, the second phase difference member, and the second member.
7. The display system according to claim 1, wherein, The values (1-DI) obtained by subtracting the depolarization index (DI) of transmitted light at a wavelength of 550 nm measured at a polar angle of 0° from 1 for both the first and second optical laminates are above 95.5%. The first optical laminate includes the polarization member, the first phase difference member, and the first member. The second optical laminate includes the reflective portion, the second phase difference member, and the second member.
8. The display system according to claim 1, comprising: A second lens portion is disposed in front of the reflective portion.
9. A display body comprising the display system according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method and apparatus for measuring weight by means of piezoelectric vibrator
JP1988200028A
Optically active liquid crystal compound having cyano group
JP1989070455A
Homeotropic alignment liquid-crystalline composition, method for producing homeotropic alignment liquid crystal film and homeotropic alignment liquid crystal film
JP2002333642A
Elliptical polarization plate and picture display device using it
JP2006163343A
Method of producing elliptically polarizing plate and image display using the elliptically polarizing plate
JP2006178389A